2008
DOI: 10.1128/jvi.02547-07
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis C Virus Inhibits Cell Surface Expression of HLA-DR, Prevents Dendritic Cell Maturation, and Induces Interleukin-10 Production

Abstract: Hepatitis C virus (HCV) chronic infection is

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
56
1
2

Year Published

2008
2008
2019
2019

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 75 publications
(68 citation statements)
references
References 43 publications
9
56
1
2
Order By: Relevance
“…Our results suggested that IRF-1 expression was significantly reduced in NS5A-expressing cells but remains unaffected in core-expressing cells, indicating a more pronounced effect of NS5A on C4 regula-tion. This observation is in agreement with our previous reports that HCV core protein does not activate IRF-1 or class II transactivator (CIITA) promoter activity (3,28). We have also observed that the basal IRF-1 expression at the mRNA level was not altered in the presence or absence of IFN-␥ compared to control hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Our results suggested that IRF-1 expression was significantly reduced in NS5A-expressing cells but remains unaffected in core-expressing cells, indicating a more pronounced effect of NS5A on C4 regula-tion. This observation is in agreement with our previous reports that HCV core protein does not activate IRF-1 or class II transactivator (CIITA) promoter activity (3,28). We have also observed that the basal IRF-1 expression at the mRNA level was not altered in the presence or absence of IFN-␥ compared to control hepatocytes.…”
Section: Discussionsupporting
confidence: 93%
“…Pervious studies have shown that increased arginase-1 or ROS generation could explain the mechanism of suppressive MDSCs in chronic virus infection (19)(20)(21). However, our study supports that upregulation of IL-10 represents the major mechanism for suppressive MDSCs in CHB patients, similar to previous reports for several other human diseases (27,38,39). These cells could spontaneously secrete bioactive IL-10 ex vivo, a feature undetectable in healthy control MDSCs.…”
Section: Discussionsupporting
confidence: 90%
“…Indeed, the immune response against herpes simplex virus was suppressed by blocking the autophagy (6). With regard to HCV, functionally impaired DC dysfunctions marked by poor DC maturation, impaired antigen presentation, and attenuated cytokine production have been reported in tissue culture models and chronic hepatitis C patients (1,22,46). In addition, reduction of cell surface expression of MHC-I in HCV genotype 1b replicon cells has been reported (55).…”
Section: Discussionmentioning
confidence: 99%